ANALISIS YURIDIS TERHADAP PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL DALAM SENGKETA PEMUTUSAN HUBUNGAN KERJA (PHK) DI INDONESIA - Michael Jonathan Tambunan; Wyna Virgia Abdillah; Ynlouie Leo Kuanata; Filbert Austin; Nicole Eustacia Leo; Stella Maxentia; Aprichie Glenn Moses Saragi; Nicholas Austin Utomo; Maudika Ramadhani Suwandi; Budiman Ginting; Andi Nova Bukit; Boy Lak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze juridically the decisions of the Industrial Relations Court (IRC) in cases of employment termination disputes in Indonesia. The research employs a normative juridical method with a descriptive-analytical approach, focusing on legal norms, court decisions, and relevant literature. The findings indicate that IRC judges generally base their decisions on factual evidence, legal provisions, and applicable regulations. In several cases, judges have attempted to uphold the principles of justice, legal certainty, and expediency, particularly in ensuring the fulfillment of workers’ rights such as severance pay and compensation. However, inconsistencies in judicial reasoning and differences in legal interpretation still occur, especially regarding the legitimacy of termination grounds such as efficiency. These inconsistencies may affect the level of legal certainty and predictability for both workers and employers. Furthermore, IRC decisions have significant implications for the protection of workers’ rights and the conduct of industrial relations practices. While the decisions tend to favor worker protection, improvements are still needed in terms of consistency, transparency, and the quality of legal reasoning. Therefore, strengthening the role of the IRC is essential to ensure fair, consistent, and reliable dispute resolution in employment termination cases.